Tingkat Pertumbuhan dan Pemanfaatan Pakan Ikan Jelawat (Leptobarbus hoevenii) Dengan Penambahan Pektin Dari Kulit Jeruk Mandarin (Citrus reticulata) - Patandianan, Greace; Nikhlani, Andi; Agustina, Agustina (Universitas Batangahari Jambi, 2026)
This research was conducted to analyze and determine the best dose of pectin addition from mandarin orange peel in feed on absolute weight growth (AWG), total length growth (TLG), specific growth rate (SGR), feed intake (FI), and feed utilization efficiency (FE). This study used an experimental method with a complete randomized design consisting of 4 treatments and 3 replicates. Each treatment was given a pectin dose of 0 (P0), 5 (P1), 10 (P2), and 15 g/kg feed (P3). Jelawat fish weighing 9-10 g were kept as many as 10 fish per container and fed at satiation with a frequency of 2 times a day for 30 days. The results showed that the addition of pectin from mandarin peel showed a significant effect on AWG, TLG, SGR, FI, and FE (P